Toward a standard ubiquitous computing framework - Modahl, Martin; Agarwalla, Bikash; Abowd, Gregory; Ramachandran, Umakishore; Saponas, Scott (Proceedings of the 2nd International Workshop on Mddleware for Pervasive and Ad-hoc Computing, 2004)
This paper surveys a variety of subsystems designed to be the building blocks from which sophisticated infrastructures for ubiquitous computing are assembled. Our experience shows that many of these building blocks fit neatly into one of five categories, each containing functionally-equivalent components. Effectively identifying the best-fit “lego pieces”, which in turn determines the composite functionality of the resulting infrastructure, is critical. The selection process, however, is impeded by the lack of convention for labeling these classes of building blocks. The lack of clarity with respect to what ready-made subsystems are available within each class often results in naive re-implementation of ready-made components, monolithic and clumsy implementations, and implementations that impose non-standard interfaces onto the applications above. This paper explores each class of subsystems in light of the experience gained over two years of active development of both ubiquitous computing applications and software infrastructures for their deployment.